Relationships among the Energy, Emergy, and Money Flows of the United States from 1900 to 2011 - Campbell, Daniel Elliott; Lu, Hongfang; Walker, Henry Allen (Frontiers in Energy Research, 2014)
Energy Systems Language models of the resource base for the U.S. economy and of economic exchange were used, respectively, (1) to show how energy consumption and emergy use contribute to real and nominal GDP and (2) to propose a model of coupled flows that explains high correlations of these inputs with measures of market-based economic activity. We examined a 3rd power law model of growth supported by excess resources and found evidence that it has governed U.S. economic growth since 1900, i.e., nominal GDP was best explained by a power function of total emergy use with exponent 2.8. We used a weight of evidence approach to identify relationships among emergy, energy, and money flows in the U.S. from 1900 to 2011. All measures of quality adjusted energy consumption had a relationship with nominal GDP that was best described by a hyperbolic function plus a constant and the relationship between all measures of energy consumption and real GDP was best described by a 2nd order polynomial. The fact that energy consumption per unit of real GDP declined after 1996 as real GDP continued to increase indicates that energy conservation or a shift toward less energy intensive industries has resulted in lower fossil fuel use and reduced CO2 emissions, while maintaining growth in real GDP. Since all energy consumption measures vs. real GDP deviated from a power law relationship after 1996; whereas, total emergy use did not, we concluded that total emergy use captured more of the factors responsible for the increase in real GDP than did energy measures alone, and as a result, total emergy use may be the best measure to quantify the biophysical basis for social and economic activity in the information age. The Emergy to Money Ratio measured as solar emjoules per nominal followed a decreasing trend from a high of 1.01E+14 semj/ in 1902 to 1.56E+12 semj/ in 2011 with fluctuations in its value corresponding to major periods of inflation and deflation over this time.